2007
DOI: 10.1158/1535-7163.mct-07-0111
|View full text |Cite
|
Sign up to set email alerts
|

Selective cell death of oncogenic Akt-transduced brain cancer cells by etoposide through reactive oxygen species–mediated damage

Abstract: We have established several glioma-relevant oncogeneengineered cancer cells to reevaluate the oncogeneselective cytotoxicity of previously well-characterized anticancer drugs, such as etoposide, doxorubicin, staurosporine, and carmustine. Among several glioma-relevant oncogenes (activated epidermal growth factor receptor, Ras, and Akt, as well as Bcl-2 and p53DD used in the present study), the activated epidermal growth factor receptor, Ras, and Akt exerted oncogenic transformation of Ink4a/Arf À/À murine astr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…It is known that ROS can activate transcription factors, including NF-κB (85). However, ROS accumulation beyond threshold levels can also inhibit NF-κB activity (89)(90)(91). We recently also showed that elesclomol, a novel small-molecule oxidative stress inducer, dramatically suppressed NF-κB activity in breast cancer cells by increasing ROS (92).…”
Section: Figure 10mentioning
confidence: 99%
“…It is known that ROS can activate transcription factors, including NF-κB (85). However, ROS accumulation beyond threshold levels can also inhibit NF-κB activity (89)(90)(91). We recently also showed that elesclomol, a novel small-molecule oxidative stress inducer, dramatically suppressed NF-κB activity in breast cancer cells by increasing ROS (92).…”
Section: Figure 10mentioning
confidence: 99%
“…For example, it is well established that the glycopeptide bleomycin, an established component of standard combination chemotherapy, destroys malignant cells based on a metal-dependent prooxidant free radical mechanism leading to DNA fragmentation (61,69 More recently, accumulative evidence suggests that induction of ROS formation and redox dysregulation is causatively involved in the chemotherapeutic efficacy of many established anticancer drugs that have traditionally not been associated with a free radical mechamism of action (76). Numerous studies have demonstrated the causative involvement of ROS formation in the mediation of cancer cell apoptosis induced by various standard chemotherapeutic agents including paclitaxel (5,6), cisplatin (30), bortezomib (114), and etoposide (266). Remarkably, it has been demonstrated that cisplatin apoptogenicity depends on formation of ROS and occurs independent of nuclear DNA damage, suggesting…”
Section: Wondrakmentioning
confidence: 99%
“…For example, the topoisomerase inhibitor etoposide (Oh et al, 2007), arsenic trioxide (Nakagawa et al, 2002), and cisplatin (Berndtsson et al, 2007) all induced cell death in various cancers through oxidative stress.…”
Section: Additional Examples Of Rons-mediated Cancer Prevention: N-3 mentioning
confidence: 99%